Preparation of Aditoprim Injection against Streptococcus suis in Pigs and a Dose Regimen Based on Pharmacokinetic-Pharmacodynamic Modeling - Wei Qu; Mengxiao Dong; Yuanhu Pan; Shuyu Xie; Zonghui Yuan; Lingli Huang (MDPI AG, 2022)
In order to effectively treat the infection of Streptococcus suis and reduce the emergence of drug-resistant bacteria, an aditoprim (ADP) injection was developed in this study. The pharmaceutical property investigation results demonstrated that ADP injection was a clear yellow liquid with 10 g ADP distributing in every 100 mL solution uniformly. Its pH value and drug content were around 6.20 and 99.35~100.40%, respectively. And quality assessment preliminarily indicated its reliable quality and stability. Additionally, the bronchoalveolar lavage fluid method was first applied to evaluate accurate ADP concentration at infection site in this study. Through pharmacodynamic assay, the MIC, MBC and MPC of ADP against Streptococcus suis CVCC 607 was 2 μg/mL, 4 μg/mL and 12.8 μg/mL, respectively. The bacteria growth inhibition curves showed that ADP was a concentration-dependent antibacterial drug, and the PK-PD model parameter of AUC/MIC was selected. The pharmacokinetic parameters of alveolar fluid evaluated by WinNonlin software revealed similar pharmacokinetic process of ADP in healthy pigs and infected pigs. Combined with pharmacokinetics-pharmacodynamics (PK-PD) modeling, the dosage regimen of 3~5 days with an interval of 12 h at 4.10 mg/kg or 5.91 mg/kg could be adopted to treat the infection of Streptococcus suis. Consequently, this ADP injection with a multi-dose protocol would be a promising antimicrobial product for efficient treatment of S. suis infection of pigs.